“She Had ‘Balls’”: Islamic Liberalism And The Modern Woman In A Contemporary Malaysian Fiction In English - Bernidick Bryan P. Hosmillo (Bina Nusantara University, 2011)
The paper wants to dissect the plurality of contemporary Malay society by focusing on the construction of woman sexuality as charged with an amalgam of Islam Parochialism that is seen as a restrictive sociopolitical mechanism and (de)concentrated modernization that decentres religious functions in contemporary Malay society and uses instead a rather ‘filtered’ Islam as colour for the contours of life. Further, the paper underscores the fictive, yet real advances of the Malay woman in terms of critical consciousness and beauty manifested in cultural materialism as both are seriously equated to power. The woman, however, with all the intellectual and material elevation intervenes with (masculine) sexualisation. Hence, the paper capitalizes thenecessity to examine the complexities of masculine sexualisation, as fortified by Western modernity, which is a process of recognizing the feminine presence that inevitably generate erotic desire to sexual fantasy that ultimately constructs the woman. The paper’s major thrust is to reconceptualise the notion of power anchored in the ideological framework of its polysemous nature. Such progressive elucidation of the concept creates tension between empowerment and domination which is a relevant concern in feminist politics and interpretations in that the specific implication of such reconceptualization is the object of becoming not oppressors, but of becoming liberated that in the discourse of Malayness is largely problematic as it is always perceived to be antithetical to revitalization of Islam through authentic Malaysian Literature in English for ‘liberalism’ in this case, is associated with the rupture of women’s sexuality.